2010
DOI: 10.1007/s10508-010-9667-3
|View full text |Cite
|
Sign up to set email alerts
|

Consensual Sex Between Men and Sexual Violence in Australian Prisons

Abstract: Estimates of the incidence of sexual coercion in men's prisons are notoriously variable and fraught with conceptual and methodological problems. In 2006-2007, we conducted a computer-assisted telephone survey of a random sample of 2,018 male prisoners in New South Wales and Queensland. Of 2,626 eligible and available inmates, 76.8% consented and provided full responses. We asked about time in prison, sexual experience, attraction and (homo/bi/heterosexual) identity, attitudes, sexual contact with other inmates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…The number of sexually active participants in our study is comparable to what other researchers in this area have reported (Richters et al 2012). Similar to our research findings, in a study of 245 female prisoners, Hensley et al (2002) found that younger and Black prisoners were more like to engage in sexual behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…The number of sexually active participants in our study is comparable to what other researchers in this area have reported (Richters et al 2012). Similar to our research findings, in a study of 245 female prisoners, Hensley et al (2002) found that younger and Black prisoners were more like to engage in sexual behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…While concern about consensual and nonconsensual sex in prisons is widely described in the literature (Haney 2011;Pardue, Arrigo, and Murphy 2011), some researchers contend that both types of sex may actually occur less frequently than is often posited (Richters et al 2012). It is not possible to assess the frequency of such acts in PNG, but non-consensual sex is a devastating crime that can have lasting physical as well as psychological and social effects and, in extreme cases, even death (Noll 2008;D'Alessio, Flexon, and Stolzenberg 2013).…”
Section: Ensuring Protection In Prisonmentioning
confidence: 99%
“…The importance of prisoners as a key population in the global epidemic was recently reinforced by the WHO guidelines for key populations (WHO 2014). Closed settings have been identified to pose a substantial risk for HIV as a result of sexual behaviour (including rape), injecting drug use and body modification practices such as tattooing (Richters et al 2012;Pinkerton, Galletly, and Seal 2007;Angora et al 2011;Krebs 2002). This is true in all countries, but especially in resource-poor settings where the prevalence of HIV in closed settings is often higher than among the general population (Angora et al 2011), thus begging the question, is HIV 'on the inside' in PNG?…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, slightly more prisoners in Queensland (8.8%) than NSW (5.8%; p=0.01) reported sexual activity in prison (see table 1). Overwhelmingly, the reported sexual activity in both states was consensual and consisted mostly of manual or oral sex 7 9. The proportion of prisoners reporting anal sex in prison was equally low in NSW (3.3%) and Queensland (3.6%; p=0.8).…”
Section: Resultsmentioning
confidence: 98%